Optimized passive thermoelectric temperature regulation for dust-resilient sensor nodes in Extreme Desert Climates - Md. Mahib Al Mamun; Rafin Ahmed; Oishik Arham Audhip; Hassan Jubair (PLoS ONE, 2026)
Autonomous sensor nodes deployed in harsh, remote desert environments face significant reliability challenges due to extreme diurnal temperature fluctuations. This paper presents an Optimized Passive Thermoelectric Temperature Regulation System designed to protect sensitive electronics and batteries from these conditions. The innovative system leverages a solid-state Peltier module for active bi-directional temperature control (cooling and heating), crucially supported by novel, highly efficient fanless passive heat transfer components. The system integrates thermoelectric regulation with optimized passive heat dissipation and solar-powered energy management, enabling continuous 24/7 operation. Experimental validation under simulated desert environments demonstrates a coefficient of performance (COP) of up to 0.83, cooling from approximately 40°C to 20°C within 4.6 minutes, and approximately 10% reduction in power consumption compared to forced-convection systems. Its holistically designed, sealed, and dust-proof enclosure, devoid of mechanical moving parts in the thermal management system (fans, compressors), drastically enhances reliability and minimizes maintenance requirements compared to traditional methods like forced air cooling or miniature vapor-compression systems. This approach uniquely addresses the compounded challenges of dust, extreme temperatures, and limited power. It offers a superior solution for ensuring the uninterrupted accuracy, extended lifespan, and demonstrated improved performance over conventional mechanisms of vital sensor nodes in arid climates.